Pengaruh Pelatihan dan Pengembangan Terhadap Kinerja Karyawan di Badan Perencanaan, Penelitian, dan Pengembangan Daerah Kabupaten Probolinggo - Rhianti, Ghefira Mia; Junaedi, Deddy (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
This research aims to determine the effect of training and development on employee performance at the Regional Planning, Research, and Development Agency (Bapelitbangda) of Probolinggo Regency. The study uses a quantitative method with an associative approach. The population in this study includes all employees of Bapelitbangda, totaling 53 respondents, who were also used as the sample through purposive sampling. Data collection techniques included questionnaires, observation, interviews, and documentation. The data were analyzed using multiple linear regression, t-test, and F-test through SPSS. The results indicate that training has a significant partial effect on employee performance, as does development. Simultaneously, training and development also significantly affect employee performance. This finding suggests that to improve employee performance, the institution must continuously enhance training and development programs tailored to job demands and employee potential.